Tetrabutylphosphonium trifluoroacetate ([P4444]CF3COO) thermoresponsive ionic liquid as a draw solution for forward osmosis process - Phang, Sook Nyan; Syed Mohd Saufi, Tuan Chik; Syamsul Bahari, Abdullah; Mazrul Nizam, Abu Seman; Malyanah, Mohd Taib (Universiti Kebangsaan Malaysia, 2018)
Forward osmosis (FO) is recognized as a potential membrane technology that utilizes low energy for water desalination. It is driven by natural osmotic pressure difference between feed solution and draw solution across semipermeable membrane. Pure water will permeate from the salinity feed water to the draw solution side. In order to produce pure water, it is necessary to find the best draw solute that exhibits high draw ability and can separate the permeated water efficiently from the draw solution. In the current study, lower critical solution temperature (LCST) thermoresponsive ionic liquid (IL) of tetrabutylphosphonium trifluoroacetate ([P4444]CF3COO) was synthesized as the draw solute for FO process. ([P4444 ]CF3COO) is dissolved in water below its critical temperature of 29C and becomes two layered above this critical temperature. [P4444]CF3COO IL showed high water flux of 0.44 LMH compared to the water flux of 0.32 LMH for the NaCl draw solute at the same draw solution concentration. Applying thermoresponsive IL as the draw solute in FO process has the potential to treat high salinity of feed stream with ease of water recovery and draw solute regeneration